Penerapan Video Tutorial Keterampilan Pembuatan Canape pada Student Club Cooking Class SDIT At-Taqwa Surabaya - Afifah Nur’aini; Nugrahani Astuti; Lucia Tri Pangesthi; Andika Kuncoro Widagdo (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
Video tutorial learning media can facilitate the teaching and learning process and can stimulate students to be active in participating in learning. This study aims to determine teacher activities, student activities, student learning outcomes, and student responses to the application of video tutorials for canape making skills in the student club cooking class SDIT At-Taqwa Surabaya. This research was conducted in class V SDIT At-Taqwa Surabaya. This type of research is a type of pre-experiment research with a "One Shot Case Study" design. The data sample in this study was class V with a total of 23 students. Data in the study were obtained by several methods, namely observation, test, and questionnaire methods. The data analysis obtained is quantitative data and analyzed descriptively. The results of this research show that 1) Teacher activities in learning get an average of 3.9 with a very good category. 2) Student activities in learning get an average of 3.7 with a very good category. 3) The learning outcomes of students in the cognitive domain received an average of 92.4, in the affective domain received an average of 93.8, while in the psychomotor domain students obtained an average of 91. 4) The results of students' responses obtained an average percentage of 97.6% with a very positive category.